Anti-inflammatory and Immunostimulant Therapy with Lactobacillus fermentum and Lactobacillus plantarum in COVID-19: A Literature Review - Harry Noviardi; Dyah Iswantini; Sri Mulijani; Setyanto Tri Wahyudi; Tatik Khusniati (Borneo Journal of Pharmacy, 2022)
Inflammatory diseases are diseases characterized by inflammatory symptoms. Acute inflammatory disease can cause dysregulation of the inflammatory immune response, thereby inhibiting the development of protective immunity against infection. Among the acute inflammatory disease is COVID-19. The initial viral infection causes the antigen-presenting cells to detect the virus through a phagocytosis mechanism in the form of macrophage and dendritic cells. Lactobacillus fermentum and L. plantarum are gram-positive bacteria potentially serving as immunomodulators caused by inflammation and immune system response. Short-chain fatty acids (SCFA) produced by Lactobacillus can induce immune response through tolerogenic dendritic cells. This probiotic bacterium can induce the production of different cytokines or chemokines. Following the results of in vitro and in vivo tests, L. fermentum and L. plantarum can induce IL-10 release to activate regulatory T-cell and inhibit tumor necrosis factor-α (TNF-α) binding activity of nuclear factor kappa B (NF-κB). Literature review showed that dysregulation of inflammatory immune response disorders due to inflammatory disease could be treated using probiotic bacteria L. fermentum and L. plantarum. Therefore, it is necessary to conduct further studies on the potential of indigenous Indonesian strains of these two bacteria as anti-inflammatory and immunostimulants.